PENINGKATAN KETERAMPILAN BERPIKIR KRITIS DENGAN MODEL DISCOVERY LEARNING BERBANTUAN GOOGLE MEET - Sindi Riana Devi; Mawardi Mawardi (JURNAL TEMATIK, 2021)
The problem of this research is less innovation learning during pandemic crisis, it makes the student critical thinking skill became low than before. The general purpose of the research is to improve student critical thinking skills by using discovery learning model assisted by google meet on 5 th class elementary school in science subject content. the type of research is classroom action research by using 2 cycle  instrument test, assesment rubric critical thinking skill, and observation sheet. The percentage of student learning outcomes in Cycle I was 74.07% and cycle II was 85.18%. Meanwhile, the analysis of critical thinking skills in the first cycle was 84.6% high category and the second cycle was 88.9% very high category.